2016
DOI: 10.1103/physrevlett.117.060401
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Dimension of a Hilbert Space Needed to Generate a Quantum Correlation

Abstract: Consider a two-party correlation that can be generated by performing local measurements on a bipartite quantum system. A question of fundamental importance is to understand how many resources, which we quantify by the dimension of the underlying quantum system, are needed to reproduce this correlation. In this Letter, we identify an easy-to-compute lower bound on the smallest Hilbert space dimension needed to generate a given two-party quantum correlation. We show that our bound is tight on many well-known cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
70
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 39 publications
1
70
1
Order By: Relevance
“…Concerning the first characterization, we provide examples for which it is tight and where the shared pure quantum states are actually pinned down completely. Second, we show that it implies lower bounds on both the dimension and the amount of entanglement of the underlying quantum state, which are device-independent tasks that have drawn much attention recently [5,8,9]. We then show that the second characterization allows us to exclude the pure state that can produce a given Bell correlation from being particular states.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Concerning the first characterization, we provide examples for which it is tight and where the shared pure quantum states are actually pinned down completely. Second, we show that it implies lower bounds on both the dimension and the amount of entanglement of the underlying quantum state, which are device-independent tasks that have drawn much attention recently [5,8,9]. We then show that the second characterization allows us to exclude the pure state that can produce a given Bell correlation from being particular states.…”
mentioning
confidence: 99%
“…The corresponding statistics of the measurement outcomes is called a Bell correlation. It has been shown that the dimension and the entanglement of the underlying quantum state can be quantified in a device-independent way using only the Bell correlation data [5,[8][9][10]. In fact, some quantum states can even be pinned down completely by their violations of particular Bell inequalities, but this is only known to be possible for some special cases [1][2][3][4][15][16][17].…”
mentioning
confidence: 99%
See 3 more Smart Citations